Datafication - Ulises A. Mejias; Nick Couldry (Internet Policy Review)
Datafication is not just the making of information, which, in one sense, human beings have been doing since the creation of symbols and writing. Rather, datafication is a contemporary phenomenon which refers to the quantification of human life through digital information, very often for economic value. This process has major social consequences. Disciplines such as political economy, critical data studies, software studies, legal theory, and—more recently— decolonial theory, have considered different aspects of those consequences to be important. Fundamental to all such approaches is the analysis of the intersection of power and knowledge.